2017
DOI: 10.1021/acsami.7b00314
|View full text |Cite
|
Sign up to set email alerts
|

Layer-Number Dependent Antibacterial and Osteogenic Behaviors of Graphene Oxide Electrophoretic Deposited on Titanium

Abstract: Graphene oxide has attracted widespread attention in the biomedical fields due to its excellent biocompatibility. Herein we investigated the layer-number dependent antibacterial and osteogenic behaviors of graphene oxide in biointerfaces. Graphene oxide with different layer numbers was deposited on the titanium surfaces by cathodal electrophoretic deposition with varied deposition voltages. The initial cell adhesion and spreading, cell proliferation, and osteogenic differentiation were observed from all the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 56 publications
0
62
0
Order By: Relevance
“…Similarly, graphene coating on the Ti alloy scaffolds also enhanced cell proliferation due to promoted adsorption of the growth factor of the seeding cells; 28 however, in some studies different observations were reported. In a study by Qiu et al, 47 increased layers of graphene coated on Ti showed less cell proliferation, and cells grown on Ti exhibited the greatest proliferation among all GO modified groups after 4 days. Indeed, increasing layer-number of GO resulted in decreased cell proliferation.…”
Section: Graphene and Metalsmentioning
confidence: 90%
See 3 more Smart Citations
“…Similarly, graphene coating on the Ti alloy scaffolds also enhanced cell proliferation due to promoted adsorption of the growth factor of the seeding cells; 28 however, in some studies different observations were reported. In a study by Qiu et al, 47 increased layers of graphene coated on Ti showed less cell proliferation, and cells grown on Ti exhibited the greatest proliferation among all GO modified groups after 4 days. Indeed, increasing layer-number of GO resulted in decreased cell proliferation.…”
Section: Graphene and Metalsmentioning
confidence: 90%
“…The metal or metalloid category consists of silicon (Si), 65 zinc oxide (ZnO), 89 28 and nitinol (NiTi). 57 Polymers include poly(L-lactide) (PLLA), 46 poly(dopamine) (PDA), 68 poly(ɛ-caprolactone) (PCL), 14,36,203 poly(ethylenimine) (PEI), 37, 82 poly(lacticcoglycolic acid) (PLGA)-tussah, 61 silk fibroin (SF), 43 polyethylene terephthalate-based artificial ligament group (PET-ALs), 78 47,65,89 and inductively coupled plasma-optical emission spectroscopy (ICP-OES) 49,71 were employed to measure the release rate of ions, and inductively coupled plasma-mass spectroscopy (ICP-MS) 64 was utilized to assess the Ca/P ratio. Additional assays and measures used for sample characterization include thermal gravimetric analysis (TGA), 37,71,82,84,87 energy dispersive X-ray spectroscopy (EDX), 33 75 swelling study, 75 weight loss measurement, 60 diametral tensile strength (DTS), 60 nanoindentation measurements, 67, 76 photoluminescence (PL) spectra, 94 elemental analysis experiment, 25 magnetometry, 25 selected-area electron diffraction (SAED), 57, 91 wettability evaluation, 89 roughness evaluation 14,28,89 and PL spectrum.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…This makes difficult to compare current results with those reported in previous papers, although some generalizations can be made. The GNP production process represents a viable solution for large-scale development of anti-biofilm devices, being low-cost, highly scalable, non-toxic, and non-oxidizing [36,37], when compared to a dry transfer technique based on a hot-pressing method [20], chemical vapour deposition coupled with a wet technique transfer (using polymethyl methacrylate or PMMA) [43], electroplating and ultraviolet reduction methods [44], evaporation-assisted electrostatic assembly processes and a mussel-inspired one-pot assembly process [45], and cathodal electrophoretic deposition [46]. Furthermore, differences in antibacterial properties might depend on the specimens (Ti-disks with commercially available sand-blasted and acid-etched surfaces) and microbial species (S. aureus) used in the present study, which were different from commercial pure Ti-plates or solid titanium and microbial species, such as Streptococcus mutans, Enterococcus faecalis, Porphyromanas gengivalis, and Escherichia coli, which have been used in other studies.…”
Section: Discussionmentioning
confidence: 99%